Magnetic parameters as proxies for anthropogenic pollution in water reservoir sediments from Mexico: an interdisciplinary approach - Chaparro, Marcos Adrián Eduardo (2020)
We assess the element pollution level of water reservoir sediments using environmental magnetism techniques as a novel approach. Although “La Purísima” Water Reservoir is an important source for multiple activities (e.g. recreational, fishing and agricultural) in Guanajuato state, it has been receiving for the last centuries a high load of pollutants by mining extraction, urbanization and land-use change from the Guanajuato Hydrological Basin. The analyses of environmental magnetism, geochemistry, X-ray energy dispersive spectroscopy, scanning electron microscopy and multivariate methods were applied to study sediments from the reservoir and basin. Accordingly, they indicate the presence of iron oxides (magnetite and hematite) and iron sulfides (pyrite and greigite), which evidences relevant differences in particle size and concentration within the water reservoir (median mass-specific magnetic susceptibility χ = 23.2 × 10−8 m3/kg), as well as with respect to the river basin sediments (median χ = 88.8 × 10−8 m3/kg). The highest enrichment factor EF values (median values of EF = 2–10 for As, Co, Ba, Cu, Cd, Ni and EF > 20 for S) are mainly associated with historical mining activities that have led to an enrichment of potentially toxic elements on these water reservoir sediments. We propose the use of concentration and grain size dependent magnetic parameters, i.e. χ, remanent magnetizations and anhysteretic ratios ARM/SIRM and χARM/χ, as proxies for Ba, Co, Cr, Ni, P and Pb pollution in these river and water reservoir sediments. Such parameters allow to evaluate this sedimentary environment, and similar ones, through useful and convenient proxies.